Interactive Media with Android Based Sign Language as an Effort to Improve Dental Health Maintenance Behaviour and Decrease Debris Index in Deaf Children - Apriyanti, Lidya Dwi; Fatmasari, Diyah; Supriyana, Supriyana; Wiyatini, Tri; Djamil, Masrifan (Jurnal Kesehatan Gigi, 2025)
Deaf children in the intervention group had 100% caries and an average debris index of 80%, indicating poor dental and oral hygiene. To address this issue, interactive media with Android-based sign language and game methods was used for engaging and enjoyable learning. This research aims is used to produce interactive media with android-based sign language as an effort to improve dental health maintenance behavior and decrease debris index in deaf children. This research method is Mixed Method and Research and Development (RD) research design. There are five stages of research, namely: information collection, model design, expert validation and revision, model testing with quasi-experimental methods with pre-test design – post-test control group design. The results of interactive media with Android-based sign language according to expert validation average 95% and p value = 0.007 (very feasible). The results of the paired data effectiveness test in the intervention group with a knowledge value of p = 0.008 with a delta value of 2.666, attitude value p = 0.005 with a delta value of 3.916, skill value p = 0.004 with a delta value of 6.250, debris index score p = 0.001 with a delta value of 1.350, compared to the control group. So that this interactive media with android-based sign language is feasible and its application is effective as an effort to improve dental health maintenance behavior and reduce debris index in deaf children.